Gates Millennium Scholars Program (GMS) Cohort 2, 2001-2006 ([Verlag nicht ermittelbar], 2013)
In 1999, the Bill and Melinda Gates foundation started the Gates Millennium Scholars Program (GMS), a 20-year initiative which intends to expand access to higher education for high achieving, low-income minority students. In addition to its academic objectives, GMS also has the goal of creating future leaders in minority groups. The program is administered by the United Negro College Fund (UNCF). In 2000, the first year of the program, over 4,000 grants were awarded to minority students who were entering college or continuing their undergraduate or graduate studies during the 2000-2001 academic year. Since then, an additional 1,000 scholarships have been awarded to outstanding freshmen every year. Awardees can receive the scholarship for up to 5 years as an undergraduate and 4 years as a graduate student. The scholarship is renewable through graduate school in math, science, engineering, library science, and education. To be eligible, students had to meet several qualifications. They must (1) be of African American, American Indian/Alaska Native, Asian American, Hispanic/Latino, or Pacific Islander background; (2) be full-time students entering college or university; (3) have a GPA of at least 3.3 on a 4.0 scale; (4) be eligible for Pell Grants; (5) be leaders in community service, extracurricular, or other activities. In order to see how GMS has impacted students and to know how to better prepare minority students for college, the Bill and Melinda Gates Foundation has commissioned a survey of recipients. The survey was distributed to Cohort 1 (award year 2000), Cohort 2 (award year 2001), Cohort 3 (award year 2002), Cohort 5 (award year 2004), and Cohort 9 (award year 2008). Cohorts are composed of both recipients and non-recipients. Non-recipients are defined as individuals who were asked to go on to the scholar confirmation/verification phase, but did not become a scholar for one or more reasons. This is an ongoing survey with the fifth, and final, follow-up occurring 18 years after high school around the age of 36. The survey included questions that address the topics of (a) social, cultural, linguistic, economic background; (b) race/ethnicity and gender patterns; (c) high school preparation and experiences; (d) the role of financial aid; (e) college choice; (f) major choice; (g) engagement and leadership in college; (h) academic achievement, persistence, and completions; (i) graduate education plans; (j) career choice and transition to the workplace; and (k) democratic values and leadership after college. Baseline, first follow-up, second follow-up, and longitudinal survey data have been collected from both recipients and non-recipients. Non-cognitive scores and College Board data are also available for Cohort 2.